Finite elements simulation of improvised explosively formed projectiles. Issue 8 (5th November 2018) - Castedo, Ricardo; Santos, Anastasio Pedro; Yenes, José Ignacio; Sanchidrián, José Ángel; López, Lina María; Segarra, Pablo
Abstract : Purpose: The purpose of this paper is to investigate the applicability of the LS-DYNA software using a Lagrangian formulation in the jet formation, flight and penetration of improvised explosively formed projectiles (EFPs). Numerical results dealing with different properties of the EFPs have been validated with a significant number of field tests. Design/methodology/approach: 2D and 3D Lagrangian models, using different material definition, are developed to reproduce the field-measured characteristics of copper- and steel-made EFPs: projectile size and velocity. After validation, the model has been extended to analyse the penetration features. Two different plasticity models have been used to describe the steel target, Plastic-Kinematic and Johnson–Cook. Findings: Despite the difficulty in characterizing a non-industrial artefact, the results show that both Lagrangian models (2D and 3D) are able to simulate the projectile size, velocity and penetration capability with errors less than 10 per cent when using the Johnson–Cook material model for both liner and target. Practical implications: These data can be used to test the penetration ability of improvised EFP's against different targets, i.e. light armoured vehicles. Originality/value: There are no references that address the application of the Lagrangian simulation of non-industrial EFPs and its validation with field tests, including penetration assessment.